Politically connected boards, family business groups and firm performance: Evidence from Indonesia. Issue 1 (10th April 2020) - Joni, Joni; Ahmed, Kamran; Hamilton, Jane
Abstract : Purpose: The purpose of this paper is to examine the association between politically connected boards (both supervisory boards [SBs] and boards of directors [BODs]) and firm performance. Design/methodology/approach: We focus on the political connections of SBs and BODs separately and estimate a quadratic model based on 1, 099 Indonesian listed firm-year observations. Additionally, we address endogeneity problem by using sample selection model, generalized method of moments (GMM), propensity score matching and lagged variables regression. Findings: We find that political connections of SBs are more significantly associated with firm performance than that of BODs. Furthermore, such an association is not monotonic, in that the relationship declines after a certain level of political connections. We also find that stand-alone firms with political connections perform better than firms belonging to family business groups. Our results are robust to alternative measures and to tests for endogeneity. Research limitations/implications: This study contributes to the literature by proposing non-linear model to incorporate the rent-seeking and resource dependence arguments. Although previous studies use regression analysis (linear model) and find mixed results on the association between political connections and firm performance, our non-linear model extends our understanding of the relationship between political connections and firm performance. We extend corporate governance literature by examining the role of political supervisory boards in the dual board system and the role of family business group in Indonesia. Several limitations are addressed to interpret all the findings. We use one period of the presidency (SBY-Susilo Bambang Yudhoyono) in Indonesia as our sample, but other regimes are not considered. We collect political connection and family business group information based on publicly data available. For politically connected firms, we do not have information whether they obtain connections through ruling parties or not. Practical implications: Practitioners (such as companies and policymakers) can use our models to consider the level of political connections that can improve corporate's performance. Additionally, they can use our findings to design corporate governance policies. Originality/value: The paper identifies the use of the non-linear model on the association between political connections and firm performance in Indonesian dual board system.